Effects of Surface Structure and Temperature on the Surface Mediation, Layer Concentration and Molecular Projection Area: Adsorption of Argon and Nitrogen onto Graphitized Thermal Carbon Black - D.D. Do; H.D. Do; D. Nicholson (Adsorption Science & Technology)
This paper is devoted to an investigation of the effects of surface structure (structure-less or structured) on the description of the adsorption isotherm and the isosteric heat of nitrogen and argon adsorption onto graphitized thermal carbon black. It was found that the surface structure had little effect on the adsorption of either argon or nitrogen at 77 K and 87.3 K. The variation of the monolayer coverage concentration was also investigated as well as the concentrations of higher layers as a function of pressure and temperature. Finally, the commonly used values for the molecular projection area of nitrogen and argon for graphitized thermal carbon black (16.2 Å 2 and 13.8 Å 2 ) were revisited. For this material, a value of 15.5 Å 2 is recommended for nitrogen at 77 K, while for the case of argon at the same temperature the recommended values of 13.8 Å 2 and 12.94 Å 2 are suggested for the reduced pressure range (0.1–0.2P/P 0 ) and (0.25–0.35P/P 0 ), respectively. A value of 14 Å 2 for argon at 87.3 K is suggested for the BET plot over the reduced pressure range of 0.1–0.2P/P 0 .